PENYULUHAN PENTINGNYA IMUNISASI TETENUS TOXOID (TT) PADA IBU HAMIL DI DESA MUARA PURBA NAULI KECAMATAN ANGKOLA MUARA TAIS TAHUN 2021 - wardayani, Eliya (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2022)
ABSTRACT Until now, the success of the TT immunization program has not achieved the expected results. The low coverage of TT is partly due to the low knowledge of pregnant women about TT immunization and attitudes that do not yet support the practice of TT immunization. One of them is the reluctance of mothers to come to Posyandu for follow-up injections. The purpose of this activity is to increase mother's knowledge about the importance of TT immunization for pregnant women in Muara Purba Nauli Village in 2021. The method used in this service is the lecture method by providing counseling to pregnant women about the importance of TT immunization for mothers and babies. The material used is in the form of leaflets which are distributed to pregnant women. In addition to mothers, counseling was also given to posyandu cadres to provide introduction and knowledge about the importance of Tentanus Toxoid Immunization for pregnant women so that the cadres could motivate pregnant women to get tetanus toxoid immunization. The result of this service is an increase in mother's knowledge about the importance of TT immunization for herself and her baby. Mothers also increasingly understand the importance of TT immunization during their pregnancy. By knowing and understanding pregnant women about TT immunization, pregnant women will carry out TT immunization to improve their health. The cadres also understand more about the importance of TT immunization. Counseling went well, mothers and cadres understood more and understood how important TT immunization during pregnancy is for the health of mothers and their babies.